Me before you [compact disc, unabridged] : a novel - Moyes, Jojo, 1969- (Penguin Audio, 2012)
Louisa Clark is an ordinary girl living an exceedingly ordinary life, and has never been farther afield than her tiny village. She takes a badly needed job working for ex-Master of the Universe Will Traynor, who is wheelchair bound after an accident. Will is acerbic, moody, and bossy. But Lou refuses to treat him with kid gloves, and soon his happiness means more to her than she expected.